Alterations of White Matter Network Properties in Patients With Functional Constipation - Peihong, Ma; Tao, Yin; Zhaoxuan, He; Sha, Yang; Li, Chen; Kunnan, Xie; Jingwen, Chen; Likai, Hou; Yuke, Teng; Yuyi, Guo; Fumin, Wang; Zilei, Tian; et al. (Frontiers in Neurology, 2021)
ABSTRACT Background: The abnormalities in brain function and structure of patients with functional constipation (FC) have been identified using multiple neuroimaging studies and have confirmed the abnormal processing of visceral sensation at the level of the central nervous system (CNS) as an important reason for FC. As an important basis for central information transfer, the role of the white matter (WM) networks in the pathophysiology of FC has not been investigated. This study aimed to explore the topological organization of WM networks in patients with FC and its correlation with clinical variables. Methods and Analysis: In this study, 70 patients with FC and 45 age- and gender-matched healthy subjects (HS) were recruited. Diffusion tensor imaging (DTI) data and clinical variables were acquired from each participant. WM networks were constructed using the deterministic fiber tracking approach, and the global and nodal properties of the WM networks were compared using graph theory analysis between patients with FC and HS. The relationship between the representative nodal characteristics–nodal betweenness and clinical parameters was assessed using partial correlation analysis. Results: Patients with FC showed increased nodal characteristics in the left superior frontal gyrus (orbital part), right middle frontal gyrus (orbital part), and right anterior cingulate and paracingulate (P < 0.05, corrected for false-discovery rate) and decreased nodal characteristics in the left caudate and left thalamus (P < 0.05, corrected for false-discovery rate) compared with HS. The duration of FC was negatively correlated with the nodal betweenness of the left thalamus (r = −0.354, P = 0.04, corrected for false-discovery rate). Conclusion: The results indicated the alternations in WM networks of patients with FC and suggested the abnormal visceral sensation processing in the CNS from the perspective of large-scale brain WM network.